2021
DOI: 10.1101/2021.05.28.21258014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Transcriptomic Severity Metric that Predicts Clinical Outcomes in Critically Ill Surgical Sepsis Patients

Abstract: Purpose: Prognostic metrics for the rapid and accurate prediction of sepsis severity that could elicit a meaningful change in clinical practice are currently lacking. Here, we evaluated a whole blood, multiplex host mRNA expression metric, Inflammatix-Severity-2 (IMX-SEV-2), for identifying septic, hospitalized patients for 30-day mortality, development of chronic critical illness (CCI), discharge disposition, and/or secondary infections. Methods: This is a retrospective, validation cohort analysis of a pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…EAS electronic alert system, SD standard deviation. The p-value was calculated using the indicated statistics: www.nature.com/scientificreports/ Many challenges and limitations can be encountered during electronic alert development, including differences in adult and pediatric parameters, the presentation timing, and the variable phenotypes of sepsis and the underpinning genomics subgroups 33,[36][37][38][39] . For instance, compared to adults, pediatric sepsis recognition is challenging due to the low specificity of tachycardia and tachypnea and the relatively late manifestation of hypotension 38 .…”
Section: Discussionmentioning
confidence: 99%
“…EAS electronic alert system, SD standard deviation. The p-value was calculated using the indicated statistics: www.nature.com/scientificreports/ Many challenges and limitations can be encountered during electronic alert development, including differences in adult and pediatric parameters, the presentation timing, and the variable phenotypes of sepsis and the underpinning genomics subgroups 33,[36][37][38][39] . For instance, compared to adults, pediatric sepsis recognition is challenging due to the low specificity of tachycardia and tachypnea and the relatively late manifestation of hypotension 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also demonstrated the potential of measuring expression of targeted mRNA transcripts from patient blood to diagnose a range of infectious diseases [38, 42, 1, 2]. Development of these host response signatures requires first identifying those genes strongly associated with a condition of interest in one or multiple studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several validated tools such as Acute Physiology and Chronic Health Evaluation (APACHE) IV and Sequential Organ Failure Assessment (SOFA) that have been used to predict sepsis mortality, there is no equivalent that predicts disease progression to more severe forms of infection among hospitalized patients without regard to mortality (4). Previous studies have attempted to use clinical methods to develop predictive models for sepsis progression (5)(6)(7)(8)(9)(10). Although there have been encouraging initial results in these studies, predictive models have not yet been demonstrated to be sufficiently generalizable to have clinical utility.…”
mentioning
confidence: 99%